Behavioural Labour Economics: Advances and Future Directions - Thomas Dohmen (Institute for the Study of Labor (IZA), 2014)
In the past decades, behavioural economics has become an influential and important field of economics. Interest in behavioural economics derives from unease with standard economic models that are based on restrictive assumptions, which confine the nature of human motivation. Although Adam Smith, the founding father of modern economics, had highlighted the multitude of psychological motives that drive human behaviour, and despite the fact that many influential economists thereafter believed in tenets of modern behavioural economics, the homo economicus assumption became prevalent, until this construct was challenged by compelling evidence on social, cognitive and emotional factors that drive decision-making and social interaction. Since human interaction is germane to labour markets, one would expect behavioural economics to be highly relevant for labour economics. This paper gauges whether and how behavioural economics has left its mark on labour economics, considers the timing and structure of this development, and contemplates its future impact on labour economics.
Keywords: J00; J01; D03; 330; behavioural economics; labour economics; behavioural labour economics